1984
DOI: 10.1056/nejm198407193110301
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Penicillin-ResistantNeisseria gonorrhoeaewith Oral Norfloxacin

Abstract: Norfloxacin, an orally administered quinoline carboxylic acid that is structurally related to nalidixic acid, has been shown to be highly active in vitro against penicillinase-producing Neisseria gonorrhoeae. Ninety-two men with culture-proved gonococcal urethritis, 46 per cent with penicillinase-producing N. gonorrhoeae, and 27 per cent with non-penicillinase-producing N. gonorrhoeae that was resistant to penicillin were given either 1200 mg of norfloxacin divided into two equal oral doses four hours apart (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1

Year Published

1986
1986
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(23 citation statements)
references
References 7 publications
0
22
1
Order By: Relevance
“…Haase et al reported a 95% cure rate with a 3-day regimen of rosoxacin (5), and Naamara et al reported 95 and 100% cure rates for a single dose and a 3-day regimen of ciprofloxacin, respectively (7). Single-day treatments with ciprofloxacin and norfloxacin were also reported to be highly effective treatment of penicillin-resistant Neisseria gonorrhoeae (3,6). Although 500 and 1,000 mg appeared equally effective in this study among Asian men, the 5% failure rate of the 500-mg single dose among African men suggests that 1,000 mg is a more reliable dosage.…”
Section: Discussioncontrasting
confidence: 39%
“…Haase et al reported a 95% cure rate with a 3-day regimen of rosoxacin (5), and Naamara et al reported 95 and 100% cure rates for a single dose and a 3-day regimen of ciprofloxacin, respectively (7). Single-day treatments with ciprofloxacin and norfloxacin were also reported to be highly effective treatment of penicillin-resistant Neisseria gonorrhoeae (3,6). Although 500 and 1,000 mg appeared equally effective in this study among Asian men, the 5% failure rate of the 500-mg single dose among African men suggests that 1,000 mg is a more reliable dosage.…”
Section: Discussioncontrasting
confidence: 39%
“…The MIC testing identified only one strain that had a ceftriaxone MIC of >0.06 ,ug/ml, and all strains had ciprofloxacin MICs of <0.03 ,ug/ml. An earlier study that used two doses of norfloxacin also had an excellent outcome (23). Regrettably, resistance to fluoroquinolones appears to emerge quickly.…”
Section: Tmp-smxmentioning
confidence: 98%
“…Ciprofloxacin, given as a single 250-mg oral dose, cured 57 cases of gonorrhea, including 7 rectal and 3 pharyngeal infections (12). Norfloxacin given orally in two 600-mg doses 4 h apart cured all of 59 cases of gonococcal urethritis, eliminating the nasopharyngeal colonization encountered in two patients (6). Very promising are the low MICs of A-56619 against C. trachomatis.…”
mentioning
confidence: 90%